Eksplorasi Batik Tulis Sari Kenongo Sebagai Sumber Belajar Etnopedagogi Di Sekolah Dasar - Sulistriyaniva, Ratna; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2024)
Primary education plays an important role in shaping students' character, identity and love for local culture. Ethnopedagogy is an educational approach that incorporates the principles of local culture into education, emphasizing the special values of each culture and fostering students' sense of responsibility for the country's history, language and traditions. However, ethnopedagogy-based learning is still not optimally implemented in primary schools due to problems such as insufficient resources and teaching materials to integrate culture. Batik tulis Sari Kenongo is one of Sidaorjo's local cultures that can be used as an ethnopedagogical teaching tool in primary schools. This research uses descriptive qualitative research methods. Descriptive qualitative method is a research method that focuses on understanding social conditions through exposure or description and interpretation in detail, emphasizing actual conditions. Data collection techniques used to collect in-depth information from various sources were conducted through (1) interviews, (2) observations, and (3) documentation studies. The research obtained information about the history, characteristic motifs, as well as techniques and ways of making Sari Kenongo handmade batik. The results also show that Sari Kenongo batik can be included in the elementary school curriculum as an ethnopedagogy-based learning resource because Sari Kenongo batik is rich in cultural values, philosophy, and social learning. So it can be concluded that batik tulis Sari Kenongo can be utilized as an ethnopedagogy-based resource to instill cultural values in students from an early age, by linking to subject matter such as fine arts, science, social science, or mathematics.